2021
DOI: 10.2147/ndt.s307394
|View full text |Cite
|
Sign up to set email alerts
|

Met and Unmet Needs in an Inpatient Psychiatry Setting in Spain

Abstract: Purpose Patients with severe mental disorder have health and social needs that require care. The aim of the study was to determine the main areas of perceived needs among inpatients with severe mental disorders and to identify risk factors of the group of patients with the greatest unmet needs. Patients and Methods A total of 150 patients with severe mental illness were assessed during admission prior to discharge from the hospital. Camberwell Assessment of Needs was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…However, studies with outpatient participants and less illness severity reported fewer needs ( 25 , 26 ). Identical to our results, numerous studies have reported high unmet patient needs for intimate relationships, sexual expression, information on condition and treatment, psychological distress, and psychotic symptoms ( 12 , 27 , 28 ).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…However, studies with outpatient participants and less illness severity reported fewer needs ( 25 , 26 ). Identical to our results, numerous studies have reported high unmet patient needs for intimate relationships, sexual expression, information on condition and treatment, psychological distress, and psychotic symptoms ( 12 , 27 , 28 ).…”
Section: Discussionsupporting
confidence: 88%
“…However, due to the differences in the studies in terms of study design, symptom severity, mental health care systems, and socioeconomic status, the number of needs cannot be compared precisely. Still, in general, studies that evaluate more severe and inpatient participants reported a more significant number of needs ( 12 , 24 ). However, studies with outpatient participants and less illness severity reported fewer needs ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations